Response of the germinable soil seed bank of temperate Leymus chinensis meadows to mowing regimes - Zhang, Zhitao; Yu, Tianqi; Xin, Xiaoping; Liu, Hongmei; Lv, Shijie; Wei, Zhijun; Han, Guodong; Yan, Ruirui (Frontiers in Plant Science, 2025)
Mowing is a primary practice in temperate L. chinensis meadows, which are severely degraded due to frequent mowing, overgrazing, and other factors, necessitating restoration and sustainable management. The natural recovery of these grasslands hinges on their germinable soil seed banks, which form the basis for future productivity. Thus, germinable soil seed banks are critical for restoring overexploited meadows. In this study, we conducted germination experiments on 135 soil samples from various depths to comprehensively analyze the germinable seed bank under different mowing regimes. The main results were as follows: (1) the germinable soil seed bank density decreased significantly with a mowing event per year (C1), and the number of perennial grass seeds and upper grass seeds also decreased under the mowing event per year; (2) the size of the germinable soil seed bank increased under the other mowing regimes (control area without mowing or grazing, CK; mowing event every 2 years, C2; mowing event every 3 years, C3; and mowing event every six years, C6) relative to that under once-a-year mowing. With increasing soil depth, the number of germinable soil seeds decreased significantly. Most of the seeds in the germinable soil seed banks were distributed in the 0–2 cm soil layer, accounting for approximately 80% of the total, and at depths of 5–10 cm, the number of seeds of upper grasses was greater than that of perennial grasses. (3). During the mowing event each year, the seed bank of germinable soil seeds significantly decreased. Mowing every 2 years provides a one-year interval for natural vegetation growth, allowing for greater retention of seeds in the germinable soil seed bank. Mowing every 6 years significantly reduces the disturbance frequency, providing ample time for plant reproduction and resulting in the accumulation of germinable seeds in the soil.